Thermomechanical model for NiTi-based shape memory alloys covering macroscopic localization of martensitic transformation. (15th June 2021) - Frost, M.; Benešová, B.; Seiner, H.; Kružík, M.; Šittner, P.; Sedlák, P.
Abstract: The work presents a thermomechanical model for polycrystalline NiTi-based shape memory alloys developed within the framework of generalized standard solids, which is able to cover loading-mode dependent localization of the martensitic transformation. The key point is the introduction of a novel austenite–martensite interaction term responsible for the strain-softening of the material. Mathematical properties of the model are analyzed, and a suitable regularization and a time-discrete approximation for numerical implementation to the finite-element method are proposed. Model performance is illustrated on two numerical simulations: the tension of a superelastic NiTi ribbon and bending of a superelastic NiTi tube.